2016
DOI: 10.5194/nhess-2015-312
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling ground deformation associated with the destructive earthquakes occurring on Mt. Etna's southeastern flank in 1984

Abstract: Abstract. The Timpe Fault System is the source of very shallow but destructive earthquakes that affect several towns and villages on the eastern flank of Mt. Etna (Italy). In 1984, several seismic events, and specifically on October 25, caused one fatality, 12 injuries and produced serious damage in the Zafferana and Acireale territories. This seismicity was mainly related to the activity of the Fiandaca Fault, one of the structures belonging to the Timpe Fault System. We inverted ground deformation data coll… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Etna. In particular [19] concluded that only 30% of the total deformation of the Pernicana Fault is attributable to co-seismic displacements and [50] showed a seismic efficiency lower than 30% for the Fiandaca Fault (see Fig. 1 for their locations).…”
Section: Discussionmentioning
confidence: 99%
“…Etna. In particular [19] concluded that only 30% of the total deformation of the Pernicana Fault is attributable to co-seismic displacements and [50] showed a seismic efficiency lower than 30% for the Fiandaca Fault (see Fig. 1 for their locations).…”
Section: Discussionmentioning
confidence: 99%